2004
DOI: 10.1103/physreve.69.061506
|View full text |Cite
|
Sign up to set email alerts
|

Ising fluids in an external magnetic field: An integral equation approach

Abstract: The phase behavior of Ising spin fluids is studied in the presence of an external magnetic field with the integral equation method. The calculations are performed on the basis of a soft mean spherical approximation using an efficient algorithm for solving the coupled set of the Ornstein-Zernike equations, the closure relations, and the external field constraint. The phase diagrams are obtained in the whole thermodynamic space including the magnetic field H for a wide class of Ising fluid models with various ra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 53 publications
0
4
0
1
Order By: Relevance
“…In zero magnetic field all fluids display a phase transition from an isotropic gas ͑IG͒ into a ferromagnetic liquid ͑FL͒. 1,2,5 This diversity illustrates that the details characterizing the magnetic interactions are indeed a͒ Electronic mail: gabriel.range@fluids.tu-berlin.de b͒ Electronic mail: sabine.klapp@fluids.tu-berlin.de crucial for the effect of external fields on the fluid. Magnetic fields cause the high-temperature critical line to disappear, and the TCP transforms into a critical point ͑CP͒ separating two magnetized phases with different densities.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In zero magnetic field all fluids display a phase transition from an isotropic gas ͑IG͒ into a ferromagnetic liquid ͑FL͒. 1,2,5 This diversity illustrates that the details characterizing the magnetic interactions are indeed a͒ Electronic mail: gabriel.range@fluids.tu-berlin.de b͒ Electronic mail: sabine.klapp@fluids.tu-berlin.de crucial for the effect of external fields on the fluid. Magnetic fields cause the high-temperature critical line to disappear, and the TCP transforms into a critical point ͑CP͒ separating two magnetized phases with different densities.…”
Section: Introductionmentioning
confidence: 94%
“…Examples for such fluids are Ising fluids, that is, fluids of spherical particles with short-range isotropic and additional ͑classical͒ Ising interactions, [1][2][3][4][5] Heisenberg fluids, 6-13 where the particle spin can rotate continuously, and ferrocolloids consisting of magnetic dipolar particles. Examples for such fluids are Ising fluids, that is, fluids of spherical particles with short-range isotropic and additional ͑classical͒ Ising interactions, [1][2][3][4][5] Heisenberg fluids, 6-13 where the particle spin can rotate continuously, and ferrocolloids consisting of magnetic dipolar particles.…”
Section: Introductionmentioning
confidence: 99%
“…This is because, generally speaking, these fluids can form ordered phases under certain thermodynamic conditions. Examples of vectorial internal degrees of freedom are electromagnetic (point) dipoles or classical “spins” in various dimensions. Among these spin fluids, the Heisenberg fluid ranks prominently. The Heisenberg fluid can be considered as a minimalistic but sufficiently realistic model to describe magnetic ordering in fluids. In addition, Heisenberg-like interactions arise in the context of amphiphilic colloids composed of antithetic materials (Janus particles). ,, …”
Section: Introductionmentioning
confidence: 99%
“…The study of the effect of magnetic fields on the phase behavior of different types of systems has attracted the attention of the scientific community mainly from the theoretical point of view. Different opinions about the effect of a magnetic field on the phase transitions of physical systems have been obtained. For instance, phase diagrams were calculated for model spin systems within the mean field approximation. , It was found that for fluids of hard spheres carrying Ising spins, an external magnetic field decreases the temperature of the gas−liquid critical point ( T c ).…”
Section: Introductionmentioning
confidence: 99%